Consistent Commercial Real Estate Market Indicators: Methodology and an Application to the German Office Market - Thomas A. Knetsch; Martin Micheli; Phil Kafke; Mario Schimmelpfennig (Review of Income and Wealth, 2025)
We develop a statistical-methodological framework for a set of core commercial real estate market indicators, which consists of a market price index, a gross rent index, and a net rental yield index, as well as a vacancy rate. We argue that the indicators should be (macro-)consistent, meaning that the asset valuation relation between the market price, rental income, yield, and vacant space of an individual property carries over to the macro indicators. In case of a bottom-up compilation of all indicators, macro-consistency is met if (1) target universes are common, (2) the granular data source is complete, and (3) price and rental yield indices are weighted with capital value shares while the rent index and the aggregate vacancy rate are weighted by rental income shares. We exemplify the established statistical-methodological framework by compiling a consistent set of annual indicators of the German office market using appraisal data from a real estate consulting company.
Keywords: 330; price index; rent index; rental yield index; vacancy rate